Aid or Influence?US Foreign Assistance to Indonesia in Islamic Point of View - Syafrina Machfud; Hamid Fahmy Zarkasyi; Khoirul Umam; Imron Mawardi (TSAQAFAH, 2025)
Drawing on critiques from Islamic Political Economy (IPE) and Islamic International Relations (IIR), this study analyses the political, economic, and geopolitical implications of United States foreign aid to Indonesia through the lens of the Islamic worldview. Using a philosophical approach, the research interprets the spiritual and ethical dimensions of the Islamic worldview through foundational sources such as the Qur’an, Hadith, and classical Islamic scholarship. The findings reveal that US foreign aid has minimal impact on economic growth. Instead, it predominantly promotes Western-style liberalization, democratization, secularism, and strategic geopolitical objectives, particularly as a counterbalance to China’s influence. This study highlights the misalignment between secular aid strategies and Islamic principles, advocating for policies grounded in the Islamic worldview. By integrating faith-based principles into the analysis of political economy and international relations, the research offers a comprehensive framework for understanding how Islamic ethics can shape governance, international relations, and economic behaviour. As a library-based exploratory study, the findings emphasize the need for further empirical validation through qualitative and quantitative methodologies. This research provides valuable insights into aligning Islamic ethical frameworks with contemporary political and economic practices.